AN INSIGHT INTO EFFECTUATION AND ITS USAGE IN PSYCHOSOCIAL ENTREPRENEURIAL RESEARCH - .J, Priyadarshini; Aggarwal, Vaneeta (International Journal of Psychosocial Rehabilitation, 2020)
This article gives a detailed insight into the concept of Effectuation which was developed by Dr Saras.D.Sarasvathy and its varied usage in Psychosocial Entrepreneurial Research. Decision making is an inevitable skill for all entrepreneurs. How do they make decisions and is there any universal principle or method behind their decision making ability? The term “Effectuation” answers this question. It is defined as “a logic of thinking that uniquely serves entrepreneurs in starting businesses”. It also creates a way to regulate a completely unpredictable and unknown future. Effectuation is a psychosocial dimension, based on heuristics which does the do-able in order to know how to run a business successfully. It offers a new perception to the old domain of entrepreneurship. This paper explores the antecedents to effectuation and also studies the impact of effectuation on new venture performance. The authors of the paper aimed to conceptually explore the mediating role of technology orientation in the relationship between effectuation and new venture performance. The model proposed by the authors incorporate a serial mediation approach and is also found to highlight the undeniable and influential role played by effectuation in entrepreneurial research. This paper can be further explored empirically by researchers and academicians in the field of entrepreneurship.